USING VOA NEWS TOWARDS THE LISTENING SKILL OF THE SECOND GRADE STUDENTS OF MAN 2 MAKASSAR - Nur Hazima Bt. Massarappi; Indah Fadhilah Rahman; Andi Asmawati (International Conference on Social and Islamic Studies, 2021)
There are many medias can be used in teaching listening skills. VOA News is one of the bestmedia that can make the students’ comprehend the content of listening material. In this study,researchers conduct the research with 2 classes. This research was aimed to examine whether ornot the use of VOA News in teaching listening skill can affect the students’ listening skill at thesecond grade students. The research design used in this research was Quasi-experimental designwith non-equivalent controlled group design. The technique used in taking the sample waspurposive sampling. Data were collected by using instrument with pre-test and post-test. To getthe result, the score of pre-test and post-test was analyzed by using a software called SPSSprogram. The first step in analyzed the data was normality test to know that the sample has beendrawn from a normally distributed population. The second step was paired t-test to calculate themean score, standard deviation, score of t-count and significant (2-tailed). The results showedthat the null hypothesis was rejected which VOA News is not effective to increase the studentslistening skill while the alternative hypothesis was accepted which VOA News is effective toincrease the students listening skill.